Evolving technology: creating kidney organoids from stem cells - Bridgette E. Drummond; Rebecca A. Wingert; Robert A. McKee; Joseph M. Chambers (AIMS Bioengineering, 2016)
The kidney is a complex organ whose excretory and regulatory functions are vital for maintaining homeostasis. Previous techniques used to study the kidney, including various animal models and 2D cell culture systems to investigate the mechanisms of renal development and regeneration have many benefits but also possess inherent shortcomings. Some of those limitations can be addressed using the emerging technology of 3D organoids. An organoid is a 3D cluster of differentiated cells that are developed ex vivo by addition of various growth factors that result in a miniature organ containing structures present in the tissue of origin. Here, we discuss renal organoids, their development, and how they can be employed to further understand kidney development and disease.